2018
DOI: 10.5114/ain.2018.77943
|View full text |Cite
|
Sign up to set email alerts
|

Changes in use and availability of cannabis among adolescents over last two decades. Situation in Poland and selected European countries

Abstract: Original article / Artykuł oryginAlny Changes in use and availability of Cannabis among adolesCents over last two deCades. situation in Poland and seleCted euroPean Countries Zmiany w używaniu i dostępność prZetworów konopi wśród młodZieży w okresie dwóch dekad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The study carried out by Wieczorek et al [ 4 ] revealed a noteworthy rise in cannabis experimentation among Polish adolescents following a reduction in severity of penalties for cannabis use. Except for the Czech Republic, this rate was higher than those observed in several other European countries, where a fall in use was more common.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The study carried out by Wieczorek et al [ 4 ] revealed a noteworthy rise in cannabis experimentation among Polish adolescents following a reduction in severity of penalties for cannabis use. Except for the Czech Republic, this rate was higher than those observed in several other European countries, where a fall in use was more common.…”
Section: Synthesismentioning
confidence: 99%
“…Despite these variations, all EU member states have implemented measures aimed at reducing the harm associated with drug use [ 1 ]. While some countries such as Poland, Germany, and the Netherlands allow for medical cannabis use, the specific policies regarding its use may differ [ 3 , 4 ]. There is also a range of approaches when it comes to policies that govern cannabis use.…”
Section: Introductionmentioning
confidence: 99%